2014
DOI: 10.1111/cobi.12279
|View full text |Cite
|
Sign up to set email alerts
|

The Biogeography of Globally Threatened Seabirds and Island Conservation Opportunities

Abstract: Seabirds are the most threatened group of marine animals; 29% of species are at some risk of extinction. Significant threats to seabirds occur on islands where they breed, but in many cases, effective island conservation can mitigate these threats. To guide island-based seabird conservation actions, we identified all islands with extant or extirpated populations of the 98 globally threatened seabird species, as recognized on the International Union for Conservation of Nature Red List, and quantified the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 48 publications
2
60
0
Order By: Relevance
“…We extracted breeding populations of critically endangered or endangered landbirds, seabirds, reptiles, and mammals from the Threatened Island Biodiversity database (32). We used populations classified as confirmed, probable, or potential breeders since 1990, with those classified as potential breeders limited to confirmed or probable breeding prior to 1990 (32,47). Data excluded sea turtles and marine mammals and were accessed November 24, 2014 and updated in January 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We extracted breeding populations of critically endangered or endangered landbirds, seabirds, reptiles, and mammals from the Threatened Island Biodiversity database (32). We used populations classified as confirmed, probable, or potential breeders since 1990, with those classified as potential breeders limited to confirmed or probable breeding prior to 1990 (32,47). Data excluded sea turtles and marine mammals and were accessed November 24, 2014 and updated in January 2016.…”
Section: Methodsmentioning
confidence: 99%
“…We did not calculate the percent of all native fauna that were demonstrated beneficiaries of mammal eradication because a full list of native insular fauna at the global scale was not available. We also noted from the database estimated human population size, if invasive mammals were estimated to be absent from the island, and, if not, how many and which invasive mammal species remained on each island (32,47). Approximate human population size reflects available census data in government reports and websites up to 2012 for each island.…”
Section: Methodsmentioning
confidence: 99%
“…These measures included the removal of invasive alien plants Rouget et al, 2003); the re-establishment of native vegetation on agricultural landscapes ; shooting, trapping or baiting invasive alien animals (Schüttler et al, 2009;Adams et al, 2014;Spatz et al, 2014;Tulloch et al, 2014). Only one study proposed to undertake pro-active, preventive management measures to minimize vectors of spreading (Reid et al, 2012).…”
Section: Overview Of the Systematic Review Findingsmentioning
confidence: 99%
“…This result holds true irrespective of whether ship rats were present on the islet housing the shearwater colony, and is rather surprising given the high vulnerability of Puffinus spp. to rats, particularly the ship rat (Lock 2006;Smith et al 2006;Jones et al 2008;Rando & Alcover 2008;Spatz et al 2014). The power analysis indicated that our experimental sample size was adequate to detect a biologically relevant difference.…”
Section: Discussionmentioning
confidence: 99%